Gas vs electric: Heating system fuel source implications on low-energy single-family dwelling sustainability performance. (September 2019) - O'Rear, Eric; Webb, David; Kneifel, Joshua; O'Fallon, Cheyney
Abstract: With an increasing interest in sustainable infrastructure, focus has been placed on cost-effective low-energy residential buildings. However, limited research has been completed on the impact of heating fuel selection on sustainability performance when evaluating low-energy building design goals. Heating fuel type is an important factor because space and water heating accounts for a significant fraction of home energy consumption. Using data from the new BIRDS v4.0 Incremental Energy Efficiency for Residential Buildings Database, this case study observes the impacts of fuel source type on a building's sustainability performance based on comparisons of low-energy and net-zero energy residential building designs in Maryland. Results suggest that low natural gas prices provide incentives to install natural-gas fired equipment when minimizing life-cycle costs is the primary goal. Meanwhile, electric heating equipment is likely to perform better economically in reaching net-zero energy performance, but with higher environmental impacts. Highlights: Low gas prices provide incentives to install gas-fired equipment when minimizing LCCs. Electric heating equipment performs better economically in reaching net-zero energy. In achieving net-zero energy, electric equipment produces higher environmental impacts. The cost-optimal design uses gas heating, saving an additional $937 over the period. Use of electric heating equipment lead to higher construction, energy and life-cycle costs.